Quality study of dried Peda fish using a greenhouse effect vent dryer. Issue 1 (January 2021) - Agustina, R; Mustaqimah,; Nurba, D; Yasar, M; Itawarnemi,
Abstract: The purpose of this study was to examine the physical and chemical characteristics of peda Tenggiri fish. Peda is a traditional processed fish product that is made by salting and then followed by fermentation. Types of fish commonly made peda include Tenggiri fish. The method used in this research was experimental and the parameters analyzed were air content, salt content, acid insoluble ash, and organoleptic. The results obtained from the initial water content of T enggiri fish reached 3 7%, it can be denied that the water content of dried peda fish in Lhokseudu village has reached SNI (8273: 20016). Based on research, the initial salt content in Tenggiri fish ranges from 3.02%, the proportion that meets the Standard National Indonesian (SNI) so that it is still safe to use. The acid-insoluble ash content of Tenggiri fish reached 5.26% during the 23-hour drying process, the acid insoluble ash content increased, therefore the acid insoluble ash content did not meet the SNI standard.